The Functions of the Executive 30th Anniversary Edition - Barnard, Chester (Cambridge Harvard University Press, 1968)
Most of Barnard's career was spent in executive practice. A Mount Hermon and Harvard education, cut off short of the bachelor's degree, was followed by nearly forty years in the American Telephone & Telegraph Company. His career began in the Statistical Department, took him to technical expertness in the economics of rates and administrative experience in the management of commercial operations, and culminated in the presidency of the New Jersey Bell Telephone Company. He was not directly involved in the Western Electric experiments conducted chiefly at the Hawthorne plant in Cicero, but his association with Elton Mayo and the latter's colleagues at the Harvard Business School had an important bearing on his most original ideas.
Includes index
Keywords: Leadership